The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.